Literary, Methodological Paradigms: The Theme of Artsakh in the Works by Raffi and Muratsan - Balayan, Zinaida (Տիգրան Մեծ)
The works “Khamsa Melikdoms” by Raffi and “Baghtasar Metropolitan Hasan-Jalaliants Brief Biog-raphy”, “Ruzan or the Patriotic Girl” by Muratsan and their comprehensive research and re-evaluation are the chapters of “Artsakh in the Armenian Literature of the XIX century” research and the primary data for the article given.In the research, the subject of Artsakh is presented within the general framework of Armenian literature of the XIX century as a literary phenomenon viewed separately.It has its traditional layers and unique documents of secular culture and art, literary, political, philo-sophical thought.
Keywords: Artsakh history; Literature